Genomic characterization of five deletions in the LDL receptor gene in Danish Familial Hypercholesterolemic subjects - Larsen Mogens L; Nielsen Gitte G; Stenderup Anette; Damgaard Dorte; Nissen Peter H; Færgeman Ole (BMC, 2006)
Abstract Background Familial Hypercholesterolemia is a common autosomal dominantly inherited disease that is most frequently caused by mutations in the gene encoding the receptor for low density lipoproteins (LDLR). Deletions and other major structural rearrangements of the LDLR gene account for approximately 5% of the mutations in many populations. Methods Five genomic deletions in the LDLR gene were characterized by amplification of mutated alleles and sequencing to identify genomic breakpoints. A diagnostic assay based on duplex PCR for the exon 7 - 8 deletion was developed to discriminate between heterozygotes and normals, and bioinformatic analyses were used to identify interspersed repeats flanking the deletions. Results In one case 15 bp had been inserted at the site of the deleted DNA, and, in all five cases, Alu elements flanked the sites where deletions had occurred. An assay developed to discriminate the wildtype and the deletion allele in a simple duplex PCR detected three FH patients as heterozygotes, and two individuals with normal lipid values were detected as normal homozygotes. Conclusion The identification of the breakpoints should make it possible to develop specific tests for these mutations, and the data provide further evidence for the role of Alu repeats in intragenic deletions.